Occurrence of Yersinia rohdei among feral reindeer (Rangifer t. tarandus) and kelp gulls (Larus dominicanus) on the Sub-Antarctic island South Georgia. Issue 1 (1st January 2018) - Bonnedahl, Jonas; Berg, Charlotte; Andersson, Dan I.; Söderlund, Robert; Vågsholm, Ivar; Olsen, Björn
ABSTRACT: Introduction: During a research expedition in 2012, faecal samples were collected from feral reindeer and kelp gulls on the main island of South Georgia in the Sub-Antarctic region of the Atlantic. The samples were analysed for bacteria of the genus Yersinia with the aim of identifying isolates to the species level.Materials and Methods: A total of 11 reindeer samples and 26 Kelp Gull samples were retrieved from the location of Stromness, kept refrigerated and cultivated for gram-negative bacteria.Results: Three of the samples showed growth of Yersinia rohdei, as confirmed by biochemical typing, MALDI-TOF and 16S rRNA sequencing. The isolates were indistinguishable from each other by 16S sequencing, and differed by a single base pair from the type strain of Y. rohdei.Discussion: The Yersinia genus contains well-known pathogens of significance to both human and veterinary medicine, but the public health and animal health relevance of Y. rohdei is unknown. Although it is clear that Y. rhodei is present in the south Georgian biotope, its importance and relevance for biological diversity is unknown, as is if this presence is merely a reflection of human activities.